2008
DOI: 10.2528/pierl07122811
|View full text |Cite
|
Sign up to set email alerts
|

A Concept of Moving Dielectrophoresis Electrodes Based on Microelectromechanical Systems (Mems) Actuators

Abstract: Abstract-A concept of moving dielectrophoresis electrodes (MDEP) based on Microelectromechanical Systems (MEMS) actuators is introduced in this letter.An example design of tuneable dielectrophoresis filter is presented. Finite Element Analysis of the electrostatic field of the tuneable filter has been conducted. Results show that the trapping force can be adjusted by actuating the MEMS actuators.The principle of the dielectrophresis (DEP) is based on polarization of the dielectric particles under electrostatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In particular, in the case of low mechanical speed, the reflection coefficient for a slow-wave is close to unit when the relative period |a/(nλ)| is near unit, while that for a fast-wave is far from unit. The results are significant for interrelated research in the fields of electromagnetics and electrodynamics, and may have promising applications in other fields such as sensors, actuators [22,23], motion or structure parameter determination, and MEMS devices [24,25].…”
Section: Discussionmentioning
confidence: 97%
“…In particular, in the case of low mechanical speed, the reflection coefficient for a slow-wave is close to unit when the relative period |a/(nλ)| is near unit, while that for a fast-wave is far from unit. The results are significant for interrelated research in the fields of electromagnetics and electrodynamics, and may have promising applications in other fields such as sensors, actuators [22,23], motion or structure parameter determination, and MEMS devices [24,25].…”
Section: Discussionmentioning
confidence: 97%
“…In the literature some works with interdigital sensors, called planar capacitive interdigital multifinger (IDCM), present many applications in the most diverse areas such as chemical, biological, microelectromechanical, telecommunications, and piezoacoustic systems [1][2][3][4][5][6] . New types of interdigital sensors having the most diverse configurations, with different numbers of electrodes, are being studied for various types of projects [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Properties of the IDC have been studied by many authors and have shown high performance when being used as sensors involved with many scientific applications. For example, interdigitated sensors are used in telecommunications, biotechnology, chemical sensing, dielectric imaging, acoustic sensors, and microelectromechanical systems (MEMS) applications [11][12][13].…”
Section: Introductionmentioning
confidence: 99%